Penerapan Metode Analytical Hierarchy Process (AHP) dalam Penentuan Penerima Bantuan Program keluarga harapan (PKH) di Kelurahan Binjai Kecamatan Medan Denai - Fauza, Gita Dwi; Dur, Sajaratud; Rakhmawati, Fibri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Poverty is the main problem and complex for every country including Indonesia. APS (Angka Partisipasi Sekolah) percentage of Indonesia is declining in the higher education. It causes the quality of the next generation to become low and trapped in a cycle of poverty. In order to accelerate poverty reduction, starting is implementing Program Keluarga Harapan (PKH). The different criterias that are used, make the companion staff find it difficult to determine the priority components of RTM (Rumah Tangga Miskin) that become PKH participants. This study aims to determine the priority of the RTM component that can be used by everyone, espesially for the PKH companion staff to be on target. The method used is the AHP method to overcome the priority criteria, which will then be sorted from the highest to the lowest, by testing 100 family data of prospective recipients of PKH assitance, obtained 95 data on families who are eligible to receive PKH assistance and 5 data on families who are not eligible to receive PKH.